Improving the photostability of silk using a covalently-bound UV absorber. (November 2015) - Chen, Weiguo; Wang, Zongqian; Cui, Zhihua; Pan, Donghui; Millington, Keith
Abstract: The covalent coupling reaction between the tyrosine residues on silk fibroin and a hydroxyphenyl benzotriazole UV absorber containing a diazonium group caused a decrease in UV–visible transmittance through silk fabric together with yellowing due to the presence of the conjugated azo-benzotriazole chromophore. After exposure to UV irradiation, untreated silk was yellowed due to photooxidation of the aromatic amino acid residues in the fibroin protein, whereas the modified silk concurrently experienced some photoyellowing of the protein, together with photobleaching of the covalently bonded conjugated chromophore. Although application of the UV absorber caused a decrease in tensile strength, modification of silk with a higher amount led to a very low color change and less decrease in tensile strength than untreated silk fabric following UV irradiation.